ARCHETYPE ANALYSIS OF PERSEUS' JOURNEY IN CLASH OF THE TITANS 2010 FILM BY LOUIS LETTERIER - Ika Fitriani; Syahruni Junaid; Masykur Rauf (UIN Alauddin Makassar, 2016)
This thesis studied about archetype analysis of Perseus’ journey in Clash of the Titans 2010 film. The aim of this research was to describe archetype patterns being reflected of Perseus’ journey in Clash of the Titans 2010 film by Louis Letterier. This research applied qualitative method where the data were analyzed through Campbell’s theory about archetype. The researcher chose note taking as the instrument of the research. The researcher found that there were six archetype characters, eight symbols of archetype symbols, and three phases of situation archetype. Therefore, this research can be concluded that Clash of the Titans 2010 film showed six archetype characters where Perseus himself as hero, eight archetype symbols, and three phases of archetype situation are separation, initiation, and return. The implication of this research is to give more information, description and comprehending about archetype. Moreover, it can be a reference for the student of Adab and Humanities faculty who attracted to observe the similar research.